Pollinator intraspecific body size variation and sociality influence their interactions with plants - Peralta, Guadalupe (2024)
1. Species morphological and behavioural traits are key determinants of which pollinator species interact with which plant species. However, individuals within species are not identical in their traits and this diversity could help us understand plant–pollinator interaction patterns.2. Using three independent data sets, we assessed whether bee intraspecific body size variation (ITV) and sociality influenced pollinator interaction specialisation, intraspecific niche partitioning, centrality in the interaction network and phylogenetic diversity of the plants visited.3. We found that solitary pollinators were more specialised in their interactions with plants and had lower intraspecific niche partitioning compared to social pollinators. Furthermore, solitary pollinators with higher ITV had higher centrality in the network and visited a higher phylogenetic diversity of plants compared to solitary species with lower ITV, whereas the opposite pattern emerged for social pollinators. Pollinator ITV did not differ between social and solitary bee species.4. Our findings show that the effect of pollinator body size variation on plant–pollinator interactions depends on pollinator species sociality. Specifically, solitary pollinators with higher ITV and social pollinators with lower ITV seem to be the most important contributors to maintaining the evolutionary diversity of the plant community, and also the species with the largest potential to affect (via cascade effects) the entire plant–pollinator network.